Spectral characteristics of electroluminescence light-emitting structures - Исмaйловa Г.А.; Яр-Мухамедова, Г.Ш.; Мұрaдов А.Д.; Үмітхaновa Г.Е. (Recent Contributions to Physics, 2016)
Investigation of the spectral characteristics of electroluminescence test light emitting structures made of SiO2/ Si simples nanocrystals obtained as a result of implantation Sn ions into the layer of silicon dioxide, with an energy of 200 keV, a dose of 1 × 1017 cm-2 and heat treatment at 900 ºC for 60 minutes in air. These samples were characterized by an intense glow, visible to the naked eye when illuminated with blue or violet laser. Using these samples, we have manufactured the initial model for electroluminescence studies, but we have not seen the light of the samples in a voltage range of -30 to 30V. The lack of light with low voltage. The thickness of the layer of silicon oxide test samples was 600 nm. For the appearance of electroluminescence in the layers of this thickness we need higher voltages, our device does not have enough voltage range.